Literature Study: Basic Concepts and Scope of Basic Education Unit Management - Rajaminsah; Lina Ningrum; Muliati Said; Wili Suminar (al-Afkar, Journal For Islamic Studies, 2024)
Incorrect education management will cause a decline in education in Indonesia in general and a decline in education in educational units in particular. On the other hand, good education management will contribute to improving the quality and quality of education so that educational goals can be achieved. Education management in basic education units starts from determining the vision, mission, goals and objectives of the education unit at the planning stage to the student output produced according to graduate competency standards at the evaluation stage. The approach in this research uses a type of literature research or library research. Library research is research carried out using library literature, whether in the form of books, notes or reports of previous research results. Management is the main force in every organization that coordinates the activities of various systems to achieve organizational goals. Based on the definition above, it can be stated that Elementary School Management is the activity of managing or managing elementary schools. There are several things that must be paid attention to in basic unit management which consists of internal and external management. And both are very sustainable in the management of basic education units.